2021
DOI: 10.1155/2021/6624378
|View full text |Cite
|
Sign up to set email alerts
|

Criterion Validity and Reliability of SF-12 Health Survey Version 2 (SF-12v2) in a Student Population during COVID-19 Pandemic: A Cross-Sectional Study

Abstract: Objective. The novel coronavirus SARS-CoV-2, responsible for the COVID-19 pandemic, led to strict domestic quarantine, social isolation policies, and consequently significant psycho-emotional and lifestyle changes. The individual and societal fear and anxiety cause significant stress affecting health-related quality of life (HRQOL). There is evidence of the psychological and mental health effects of the current pandemic on students, who are known to be a vulnerable population. A decrease in physical activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Furthermore, high levels of perceived stress and low mental health-related quality of life were observed in the examined sample. The PSS mean score is consistent with that reported for a large general population Italian sample during the first COVID-19 lockdown [52] and significantly higher than those found in samples of university students in the same period [53,54], whereas the mean standard score observed for the SF-12 index MCS is inferior in comparison with that reported in a similar sample during the COVID-19 pandemic [55] and almost two standard deviations lower than the mean score for the Italian normative population [47]. Since restrictive measures with several periods of lockdown have been adopted in Italy between 2020 and 2021, such alarming results are likely to be attributable at least in part to the well-documented impact of the pandemic and the related policies on mental health [56], with seemingly worse outcomes reported for young people [57,58].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, high levels of perceived stress and low mental health-related quality of life were observed in the examined sample. The PSS mean score is consistent with that reported for a large general population Italian sample during the first COVID-19 lockdown [52] and significantly higher than those found in samples of university students in the same period [53,54], whereas the mean standard score observed for the SF-12 index MCS is inferior in comparison with that reported in a similar sample during the COVID-19 pandemic [55] and almost two standard deviations lower than the mean score for the Italian normative population [47]. Since restrictive measures with several periods of lockdown have been adopted in Italy between 2020 and 2021, such alarming results are likely to be attributable at least in part to the well-documented impact of the pandemic and the related policies on mental health [56], with seemingly worse outcomes reported for young people [57,58].…”
Section: Discussionsupporting
confidence: 87%
“…Other studies revealed that, regardless of the level of physical activity, COVID-19 and quarantine significantly decreased the quality of life of both male and female students [ 50 ]. Students who did not engage in physical activity during confinement reported a lower level of mental health [ 51 ]. Furthermore, tobacco and cannabis use was found to be associated with excessive alcohol consumption among students [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…This outcome research study was conducted by healthcare professionals at Sapienza University of Rome and ROMA—Rehabilitation & Outcome Measures Assessment Association. The research group has carried out many outcome measures in Italy [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%